1996
DOI: 10.4319/lo.1996.41.6.1169
|View full text |Cite
|
Sign up to set email alerts
|

Bacterioplankton community structure: Protists control net production and the proportion of active bacteria in a coastal marine community

Abstract: A series of dialysis experiments was performed to study the relative importance of substrate limitation and grazing in controlling the proportion of active cells of coastal marine bacterioplankton. The grazer community was manipulated by filling dialysis bags with unfiltered water and water serially passed through 150-, 40-, and O.&pm pore-size filters. The total number of bacteria, the number of metabolically active cells, bacterial loss rates, and the abundances of heterotrophic nanoflagellates were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
184
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 243 publications
(209 citation statements)
references
References 28 publications
(33 reference statements)
23
184
0
2
Order By: Relevance
“…3, Table 1). In addition, we observed that uptake rates of FLB with a mean size of 0.94 × 0.58 µm (volume = 0.230 µm 3 ) were very similar to ingestion rates of 0.6 µm spherical beads (volume = 0.113 µm 3 , Fig. 7).…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…3, Table 1). In addition, we observed that uptake rates of FLB with a mean size of 0.94 × 0.58 µm (volume = 0.230 µm 3 ) were very similar to ingestion rates of 0.6 µm spherical beads (volume = 0.113 µm 3 , Fig. 7).…”
Section: Discussionsupporting
confidence: 55%
“…This contradiction is probably explained by a misinterpretation of data derived from using spherical latex beads as food surrogates. For example, a spherical latex bead with a diameter of 0.6 µm corresponds to a volume of 0.113 µm 3 . A filter feeding ciliate will most probably select for the diameter of a spherical prey or for the width of a rod-shaped particle, but not for the prey volume.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations